The Effect of Using the Audio-Visual Media “The Origins of Kediri” on the Short Story Writing Skills of Grade XI at SMAN 4 Kediri - Armandasari, Devi; Endang Waryanti; Andri Pitoyo (Universitas Swadaya Gunung Jati, 2025)
Indonesian language learning aims to help students develop language skills through various activities such as reading, writing, speaking, and listening. The use of media can influence students' writing skills. Audio-visual media, especially those based on regional culture and language, can improve students' understanding of the language they are learning. This study also found that the use of the audio-visual media